Active targeting theranostic iron oxide nanoparticles for MRI and magnetic resonance-guided focused ultrasound ablation of lung cancer. (May 2017) - Wang, Zhongling; Qiao, Ruirui; Tang, Na; Lu, Ziwei; Wang, Han; Zhang, Zaixian; Xue, Xiangdong; Huang, Zhongyi; Zhang, Siruo; Zhang, Guixiang; Li, Yuanpei
Abstract: Despite its great promise in non-invasive treatment of cancers, magnetic resonance-guided focused ultrasound surgery (MRgFUS) is currently limited by the insensitivity of magnetic resonance imaging (MRI) for visualization of small tumors, low efficiency of in vivo ultrasonic energy deposition, and damage to surrounding tissues. We hereby report the development of an active targeting nano-sized theranostic superparamagnetic iron oxide (SPIO) platform for significantly increasing the imaging sensitivity and energy deposition efficiency using a clinical MRgFUS system. The surfaces of these PEGylated SPIO nanoparticles (NPs) were decorated with anti-EGFR (epidermal growth factor receptor) monoclonal antibodies (mAb) for targeted delivery to lung cancer with EGFR overexpression. The potential of these targeted nano-theranostic agents for MRI and MRgFUS ablation was evaluated in vitro and in vivo in a rat xenograft model of human lung cancer (H460). Compared with nontargeting PEGylated SPIO NPs, the anti-EGFR mAb targeted PEGylated SPIO NPs demonstrated better targeting capability to H460 tumor cells and greatly improved the MRI contrast at the tumor site. Meanwhile, this study showed that the targeting NPs, as synergistic agents, could significantly enhance the efficiency for in vivo ultrasonic energy deposition in MRgFUS. Moreover, we demonstrated that a series of MR methods including T2-weighted image (T2WI), T1-weighted image (T1WI), diffusion-weighted imaging (DWI) and contrast-enhanced T1WI imaging, could be utilized to noninvasively and conveniently monitor the therapeutic efficacy in rat models by MRgFUS.